If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 5) = ex Reorder the terms: 3(5 + x) = ex (5 * 3 + x * 3) = ex (15 + 3x) = ex Solving 15 + 3x = ex Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1ex' to each side of the equation. 15 + -1ex + 3x = ex + -1ex Combine like terms: ex + -1ex = 0 15 + -1ex + 3x = 0 Add '-15' to each side of the equation. 15 + -1ex + -15 + 3x = 0 + -15 Reorder the terms: 15 + -15 + -1ex + 3x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -1ex + 3x = 0 + -15 -1ex + 3x = 0 + -15 Combine like terms: 0 + -15 = -15 -1ex + 3x = -15 Reorder the terms: 15 + -1ex + 3x = -15 + 15 Combine like terms: -15 + 15 = 0 15 + -1ex + 3x = 0 The solution to this equation could not be determined.
| 2x+1=1-3x | | y+9=-5(x+6) | | 12x^2-26=x | | 72=-84-24 | | 0.3x^2-x=0 | | 7x-9*3=5x-6 | | y+10=7(x-9) | | -8+49r^2=-4 | | 8y-12=4y+8 | | y=85+10x | | -7=1-2b-2b | | 2(x+4)=5+2x | | 44=-7f-5 | | (4x+2)+(3x+19)=180 | | 4b-8=10-3b | | 0.33x^2-x=0 | | 10n+98=-872 | | 3=1/x | | -7(-1+5v)-5v=-39+6v | | 4(2y-5)+5y=7 | | 5x+4=8x-12 | | 6x-12-2x=5x-2 | | -4=-4r+32 | | 4-5v=-46 | | -1.5=x-0.1/0.2 | | 7(v+75)=938 | | -2+6(5b-4)=7(b+4)+5b | | -22=-13r+4 | | 5r^3(2r^1/2) | | 8+10m-1=7m+21-4m | | y=y-y | | y+5=10(x+9) |